Population structure and reproductive cycle of the commercial sea cucumber Holothuria mexicana (Echinodermata: Holothuroidea) in Belize - Rogers, Arlenie; Hamel, Jean-François; Mercier, Annie (Revista de Biología Tropical, 2018)
The population and reproductive biology of the commercial sea cucumber Holothuria mexicana (Ludwig, 1875) was studied in Southern Belize (Caribbean Sea), including the sex ratio, size at sexual maturity and reproductive cycle, as well as the size structure among habitats located inside and outside protected areas. Individuals found inside marine protected areas were consistently larger than individuals found outside these boundaries. The male:female sex ratio was 1.1:1.0 with a unimodal size distribution composed mainly of sexually mature individuals (87 %). Size at sexual maturity was established to be ~10 cm based on measures of gamogenetically mature individuals during the peak of the gametogenic maturity period. Juveniles and small adults measuring ≤ 15 cm (13 %), were collected exclusively in sandy and muddy areas of seagrass habitats associated with mangroves. Larger adults were commonly found on hard substrates in both seagrass-associated and coral-reef-associated habitats. Based on histology and gonad indices, the first sign of early gametogenesis was detected in August in both sexes. Gametes developed and matured throughout the colder months between November and February. Decreases in gonad index in both years suggest annual spawning, starting in March-April 2014 (single major event) and March-April and July-August 2015 (two smaller events) for both males and females. The spawning periods were correlated with warmer or increasing temperatures, low rainfall and increasing or high chlorophyll-a concentrations. These data will hopefully guide management and protection of the natural populations of H. mexicana, which are already suffering from overfishing in Belize and neighboring countries.